2015
DOI: 10.1039/c4tc02310b
|View full text |Cite
|
Sign up to set email alerts
|

Two-step-route to Ag–Au nanoparticles grafted on Ge wafer for extra-uniform SERS substrates

Abstract: Ag–Au nanoparticles grafted on Ge wafer were fabricated as SERS substrates to detect 200 random spots and the lowest relative standard deviation of less than 7% was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Another advantage of GRR is that the reaction time can be controlled within several minutes to several hours by controlling the concentration of reactants, selecting appropriate reaction solvents and adding additives . Despite these advantages, metal or alloy particles formed by GRR can only be deposited on the surface of solid semiconductor substrates . GRR has been directly applied to noble metal nanocrystals such as Au, Ag, Pd, and Pt on semiconductor substrates.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Another advantage of GRR is that the reaction time can be controlled within several minutes to several hours by controlling the concentration of reactants, selecting appropriate reaction solvents and adding additives . Despite these advantages, metal or alloy particles formed by GRR can only be deposited on the surface of solid semiconductor substrates . GRR has been directly applied to noble metal nanocrystals such as Au, Ag, Pd, and Pt on semiconductor substrates.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…[31] For example, Ag-NPs were decorated on Ge nanowires or Ge wafers through galvanic displacement to obtain highly sensitive SERS substrates. [32][33] We also constructed Ag-NPs-decorated Ge-nanowhiskers (Ge-NWHKs) grafted on Si-micropillars which present both ultra-high sensitivity and good reproducibility. [34] However, all these SERS substrates are rigid, which are not conducive in some applications, that need flexible and bendable substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The electric field distribution by finite difference time domain (FDTD) simulation proved the high sensitivity and reproducibility of these substrates, achieving a minimum RSD of less than 7% by using R6G (1 × 10 −9 M) as a probe molecule in the aqueous detection and a RSD of less than 8% for crystal violet solution (1 × 10 −8 M). 192 In addition, they developed the bi-functional Au–FeS (Au–Co 3 O 4 ) composites by in situ reduction of Au nanoparticles on the surface of FeS (Co 3 O 4 ). They confirmed that this composite material has an inherent peroxidase-like activity, which could decompose H 2 O 2 into hydroxyl radicals, and then degrades organic contaminants into small molecules.…”
Section: Introductionmentioning
confidence: 99%